Monitoring DNA contamination in handled vs. directly excavated ancient human skeletal remains. - Elena Pilli; Alessandra Modi; Ciro Serpico; Alessandro Achilli; Hovirag Lancioni; Barbara Lippi; Francesca Bertoldi; Sauro Gelichi; Martina Lari; David Caramelli (PLoS ONE, 2013)
Bones, teeth and hair are often the only physical evidence of human or animal presence at an archaeological site; they are also the most widely used sources of samples for ancient DNA (aDNA) analysis. Unfortunately, the DNA extracted from ancient samples, already scarce and highly degraded, is widely susceptible to exogenous contaminations that can affect the reliability of aDNA studies. We evaluated the molecular effects of sample handling on five human skeletons freshly excavated from a cemetery dated between the 11 to the 14(th) century. We collected specimens from several skeletal areas (teeth, ribs, femurs and ulnas) from each individual burial. We then divided the samples into two different sets: one labeled as "virgin samples" (i.e. samples that were taken by archaeologists under contamination-controlled conditions and then immediately sent to the laboratory for genetic analyses), and the second called "lab samples"(i.e. samples that were handled without any particular precautions and subject to normal washing, handling and measuring procedures in the osteological lab). Our results show that genetic profiles from "lab samples" are incomplete or ambiguous in the different skeletal areas while a different outcome is observed in the "virgin samples" set. Generally, all specimens from different skeletal areas in the exception of teeth present incongruent results between "lab" and "virgin" samples. Therefore teeth are less prone to contamination than the other skeletal areas we analyzed and may be considered a material of choice for classical aDNA studies. In addition, we showed that bones can also be a good candidate for human aDNA analysis if they come directly from the excavation site and are accompanied by a clear taphonomic history.